Modelling Waiting Times in an Emergency Department in Greece During the Economic Crisis. (December 2018) - Manolitzas, Panagiotis; Stylianou, Neophytos
Overcrowding is one of the most common phenomenon at the emergency departments of the hospitals across the world. The aforementioned phenomenon causes many problems such as long waiting times for patients, increasing length of stay, patient dissatisfaction, ambulance diversions in some cities, prolonged pain and suffering, violence and miscommunication between the medical staff and the patients, patients leaving the emergency department without been seen and decreased physician productivity. This article analyses the problem of the increased waiting times in a Greek emergency department during the economic crisis. We use statistical models in order to reveal the factors that can lead to a decrease in waiting times. Our findings suggest that Greece's Department of Health should standardize an uppermost waiting time for emergency departments which could help improve health care.